The Development and Use of the NASIG Core Competencies for Electronic Resources Librarians. Issue 2 (3rd April 2017) - Sutton, Sarah W.; Sullenger, Paula
ABSTRACT: The Core Competencies for Electronic Resources Librarians was adopted by NASIG in 2013 and provides a framework to assess skills needed for electronic resources management. In this column, Sarah Sutton, whose graduate dissertation research led to the creation of the NASIG task force responsible for developing the core competencies, describes the development and adoption of the core competencies. Paula Sullenger describes the application of the core competencies at two institutions: Auburn University and Texas A&M University. The competencies have supported libraries in reorganization efforts as well as assessing current staff to identify gaps in skills and more effectively manage electronic resources. They have also been used to assess Library and Information Science (LIS) curricula. It is important that the core competencies be reviewed and revised to ensure their enduring relevancy within the profession.